2008
DOI: 10.1007/s10840-007-9188-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of irrigated energy application on the right coronary artery hemodynamics: FFR measurement in patients who underwent ablation of common type atrial flutter

Abstract: Ablation of AFlu did not alter RCA morphology; simultaneous FFR measurement showed severe depression of the FFR in a few patients, consistent with impairment in myocardial perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…17 Whether there really was subclinical spasm in these cases is unknown, although it was certainly plausible given the data regarding RFA at the CTI or mitral isthmus. 39,40 The other important related question is whether nitroglycerin should be administered before PFA near a coronary artery, or whether parenteral nitroglycerin should simply be ready for use if ECG changes are observed. Although either approach is probably reasonable, we do believe that administration before treatment will prove more effective than after-the-fact administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Whether there really was subclinical spasm in these cases is unknown, although it was certainly plausible given the data regarding RFA at the CTI or mitral isthmus. 39,40 The other important related question is whether nitroglycerin should be administered before PFA near a coronary artery, or whether parenteral nitroglycerin should simply be ready for use if ECG changes are observed. Although either approach is probably reasonable, we do believe that administration before treatment will prove more effective than after-the-fact administration.…”
Section: Discussionmentioning
confidence: 99%
“…17 Whether there really was subclinical spasm in these cases is unknown, although it was certainly plausible given the data regarding RFA at the CTI or mitral isthmus. 39,40…”
Section: Discussionmentioning
confidence: 99%
“…In complex AF procedures, ablation of substrate is not limited to the LA [25]. It has been shown that RF ablation of cavo-tricuspid isthmus could be accompanied by temporary but significant reduction of fractional flow reserve (FFR) in 21.2% of patients, or rarely by acute occlusion of distal segment of right coronary artery with inferior myocardial infarction [188,189]. A coronary artery injury induced with RF ablation usually is treated by emergency percutaneous coronary procedure with artery recanalization and stenting [3,187].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 99%
“…Interestingly, in a small study of patients undergoing isthmus ablation using irrigated tip catheters (≤50 • C/≤50 W), Meissner et al did not show significant angiographic changes but did demonstrate significant depression of functional flow reserve of the RCA during ablation in ∼20% of patients. 11 The flow reserve returned to normal in all cases. One possible explanation for the differential rates of RCA involvement between these studies is that the younger pigs have much smaller hearts with thinner walled atria and thus are possibly more comparable to children rather than adults.…”
Section: Discussionmentioning
confidence: 81%
“…Using 4‐mm nonirrigated tip ablation catheters with clinically applicable RF delivery settings (75°C for 30 seconds), Paul et al demonstrated that at 6 months postisthmus ablation 80% of the animals had lymphocytic infiltration extending into the RCA, and that in 40% of these there was associated narrowing of the RCA. Interestingly, in a small study of patients undergoing isthmus ablation using irrigated tip catheters (≤50°C/≤50 W), Meissner et al did not show significant angiographic changes but did demonstrate significant depression of functional flow reserve of the RCA during ablation in ∼20% of patients 11 . The flow reserve returned to normal in all cases.…”
Section: Discussionmentioning
confidence: 95%